Cerebral phaeohyphomycosis due to Cladophialophora bantiana in an immunocompetent individual: A case report and brief review of literature - Prachala Rathod; Bibhabati Mishra; Archana Thakur; Poonam Loomba; Abha Sharma; Ashish Bajaj; Madhusmita Das; Ashna Bhasin (Mazandaran University of Medical Sciences, 2020)
Background and Purpose: Fungal infections of the central nervous system (CNS) are life-threatening conditions that are frequently misdiagnosed with bacterial and viral CNS infections. Cerebral phaeohyphomycosis is a cerebral infection caused by dematiaceous fungi, especially Cladophialophora bantiana. Very few cases of fungal CNS infection have been reported across the world. High clinical suspicion should be cast for the patients with brain abscess that do not respond to conventional antibiotic therapy. Case report: We report a case of a 21-year-old male presenting with headache, seizures and weakness in the limbs. Radiological examination revealed multiple brain abscesses. After surgical excision and laboratory evaluation, it was found to be caused by C. bantiana. The patient's outcome was good with surgical excision and voriconazole therapy. Conclusion: Brain abscess caused by C. bantiana is on rise, especially in immunocompromised groups. Thus, high clinical suspicion, accurate diagnosis and management are the fundamentals for good prognosis.